Reading for Seeking Main Idea in Daily Life Using a Set Of Exercises for Seeking Main Idea in Daily Life - ผาคำ ปภัสรา (Ganesha Journal, 2018)
Reading for seeking main idea in daily life using a set of exercises for seeking main idea in daily life which was a quantitative research for the 2nd year students in 2nd semester, B.E. 2560 academic year aimed to 1) Create and find the efficiency of exercises as a standard criteria 80/80, 2) Compare the pre-post achievement of studying with a set of exercises for seeking main idea in daily life, and 3) evaluate satisfactory of 2nd year students on a set of exercises. The sample was the 2nd year students of Education Faculty of Lampang Rajabhat University of 2nd semester, B.E. 2560 academic year, the number of 32 selected from Cluster Random Sampling. Tools were 8 sets of innovative exercises, test of learning achievement 50 items, and evaluation form of using these exercises 10 items. Statistical analysis was percentage, average, standard deviation (S.D), t-test, and statistical program. The finding found as following: The efficiency of a set of exercises for seeking main idea in daily was 86.44./84.94 which was higher than standard criteria (80/80). The achievement of 2nd year students after using a set of exercises (post-test) for seeking main idea in daily life was higher than before studying (pre-test) with statistical significance at .05. The 2nd year students had a satisfaction on a set of exercises for seeking main idea in daily life at high level of all. The average score was 4.78.